PERANCANGAN PROTOTYPE APLIKASI SMART RESIDENCE BERBASIS ANDROID - Asep Deden Rahmat S; Rysa Sahrial (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Basically a safe and comfortable environment is a condition that must be realized, for the sake of the continuation of harmonious and harmonious neighbourhood. Technological advances that are increasingly developing, can be used to make it easier to monitor and control security in an environment, with an application that can help in terms of security control. So that a smart environment can be realized that uses technology in managing various things. This study proposes the design of an Android-based smart residence security system. This smart residence security system uses the Agile Development Methods system development method with the extreme programming model. This research produces a prototype of an Android-based smart residence security system that has the ability to provide access to housing and community security, so that it is expected to assist in fast and precise security management.